2000
DOI: 10.3189/172756500781833331
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of the ice sheet in western Dronning Maud Land, East Antarctica: impacts of present, past and future climates

Abstract: ABSTRACT. Time-dependent ice-sheet modelling of a 176 000 km 2 area in western Dronning Maud Land, East Antarctica, provided information on the ice sheet's response to six climate-change scenarios. Another experiment was done to study changes in ice thickness, flow and basal temperature conditions between the present ice configuration and a simulated maximum palaeo-ice sheet.The input to the model included new datasets of bed and surface topography compiled for this study. The results of the six climatechange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…The surface of the major part of the East Antarctic Plateau ice sheet may have been about 100 m lower in the last glacial than at present (Jouzel et al, 1989;Pattyn, 1999;Ritz et al, 2001). In contrast, the surface elevation at the margins of the plateau may have been hundreds of meters higher (Näslund et al, 2000;Hättestrand and Johansen, 2005).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 95%
See 1 more Smart Citation
“…The surface of the major part of the East Antarctic Plateau ice sheet may have been about 100 m lower in the last glacial than at present (Jouzel et al, 1989;Pattyn, 1999;Ritz et al, 2001). In contrast, the surface elevation at the margins of the plateau may have been hundreds of meters higher (Näslund et al, 2000;Hättestrand and Johansen, 2005).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 95%
“…As only limited geomorphological information on LGM geometry is available (Näslund et al, 2000;Hättestrand and Johansen, 2005), at least the first two of these items are largely undetermined. Additionally the computational effort required to run a full-Stokes model for such a long period, with relatively unconstrained geometrical evolution, renders a prognostic simulation from LGM a highly unrealistic approach.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Equilibration times for the ice sheet to respond to changes in climate are only in the order of a few thousands of years [Näslund et al, 2000], and a reduction in temperature of the ice sheet by 10°C increases its stiffness by about 3.5 times [Paterson, 1994]. Slight changes in ice thickness could result in different surface slopes and thus velocities.…”
Section: Crymentioning
confidence: 99%
“…Ice from the first 500 m of the flow line (>50 thousand years old) originates from more than 10 km away. The northern small BIA (Figure 4) contains relatively young ice as it is an open-type BIA, and accumulation rates and velocities outside the valley [Näslund et al, 2000] are much higher than within it ( Figure 5). The small accumulation area inside the valley supplies ice that is up to 20 thousand years old to the main BIA.…”
Section: Heimefrontfjella Scharffenbergbotnen (Sbb)mentioning
confidence: 99%
“…Upland areas of the territory are highly likely to have been a nucleation site for early development of Antarctic ice (DeConto & Pollard, 2003;Jamieson & Sugden, 2008), and they are likely to act as a key pinning point of the present-day EAIS. Modelling suggested that the majority of ice within DML is cold-based at present (Näslund, Fastook, & Holmlund, 2000). Given the potential for landscape preservation under such non-erosive ice, it is possible that the subglacial DML uplands may contain evidence for earlier, smaller ice conditions, with the possibility that landforms could have been preserved since the 14 Ma expansion of Antarctic ice or even EAIS inception at 34 Ma.…”
Section: Study Areamentioning
confidence: 99%